P280 Prognosis of patients with Crohns Disease in transmural remission with gastrointestinal ultrasound. (21st January 2022) - Nylund, K; Sævik, F; von Volkmann, H L; Gilja, O H
Abstract: Background: Gastrointestinal ultrasound (GIUS) can be used to measure bowel wall thickness (BWT). If the bowel wall is less than 3 mm in all bowel segments in a patient with Crohn's disease(CD) this predicts endoscopic remission with a high degree of accuracy, but still some CD patients with disease located to the terminal ileum and colon will have a thickened bowel wall even if they are in endoscopic remission. Could BWT be an independent predictor of disease activity in CD? The aim of the study was to investigate if a normalisation of bowel wall thickness in CD patients affects risk for important negative clinical endpoints such as need for corticosteroids, failure in maintenance treatment, hospital admissions and surgery. Methods: Patients with CD referred to the Haukeland University Hospital for ileocolonoscopy were examined with GIUS and followed for at least 12 months. The clinical endpoints examined were defined as the need for short- or long-time treatment with corticosteroids, changes in the maintenance treatment including drug switch and dose adjustments, hospital admissions and any surgical procedure that could be related to Crohn's disease. Patients were categorized into 3 groups according to their findings on endoscopy and GIUS: The activity group (1) consisted of patients with activity on GIUS defined as any bowel wall segment ≥3mm and Simple Endoscopic score of Crohn's disease (SES-CD) >2. The group in transmural remission (2) was defined as all patients with BWT <3mm independent of findings on endoscopy. The final group (3) consisted of the patients with isolated endoscopic remission defined as SES-CD ≤2 and BWT ≥3mm in one or more bowel segment. Results: 155 CD patients were included in the study. In total 61/155 patients experienced one or more negative, clinical endpoint during the one year follow up period. 9/155 received treatment with corticosteroids, 50/155 had adjustments in their medical therapy, 32/155 were admitted to the hospital at least once and 18/155 had surgery. In group 1, 44/92 experienced one or more endpoints while the corresponding numbers were 9/40 in group 2 and 8/23 in group 3. The frequency of clinical endpoints were significantly different between the different groups (p=0, 020, Fischer's exact test). Only patients in group 1 were operated. Conclusion: The group with transmural remission had fewer patients with negative, clinical endpoints which suggests that GIUS is well suited for distinguishing between CD patients with high or low risk for negative clinical endpoints.